Association of Bisphenol A Exposure With Hypertension and Early Macrovascular Diseases in Chinese Adults: A Cross-Sectional Study - Wang, Tiange (Medicine (Baltimore), 2015)
Bisphenol A (BPA) is an environmental endocrine disruptor that has been associated with cardiovascular outcomes in previous observational studies. We aimed to examine the relationships of urinary BPA levels with hypertension and early macrovascular diseases. This is a cross-sectional study. From June through August 2009, 3246 participants ages 40 years or older were enrolled from Baoshan District, Shanghai, China. Logistic regression modes were used to estimate the odds ratios (ORs) for prevalent risk of hypertension, elevated carotid intima-media thickness (CIMT), arterial stiffness, and peripheral artery disease (PAD) with multivariable adjustment. We also performed stratification analysis by age and sex. The median (interquartile range) for BPA was 0.81 (0.48, 1.45) ng/mL, which is notably lower than previously reported in the United States and other Western countries. Urinary BPA concentrations were negatively associated with hypertension (multivariable-adjusted OR for the highest versus lowest BPA quartile = 0.61; 95% confidence interval [CI]: 0.46, 0.80), elevated CIMT (OR = 0.64; 95% CI: 0.47, 0.87), and arterial stiffness (OR = 0.62; 95% CI: 0.44, 0.87). The corresponding OR for PAD (60 cases total) was not significant (OR = 0.89; 95% CI: 0.28, 2.80). The negative associations of BPA with hypertension, elevated CIMT, and arterial stiffness were consistent by age and sex stratifications, and were stronger among participants ≥60 versus <60 years of age, and among women than men. In contrast with previous investigations, our study suggests negative associations of BPA exposure with hypertension and early macrovascular diseases among middle-aged and elderly Chinese. Future investigations are needed to draw more definite conclusions and generalize to other populations.